Optimal sensing performance for cooperative and non-cooperative cognitive radio networks - Waqas Khalid; Heejung Yu (International Journal of Distributed Sensor Networks)
Spectrum sensing has gained new aspects with the advent of cognitive radio and opportunistic spectrum access techniques. Spectrum sensing plays a vital role in cognitive radio networks, and its reliability determines the success of transmission. It also enables the spectrum access for unlicensed users, enhancing the spectral utilization. The successful integration of primary users and secondary users requires the secondary users to be capable of efficient sensing and keeping precise track of the primary transmissions. There exists an inherent sensing-throughput trade-off in the time-division multiple access–based hierarchical cognitive radio networks. The sum rates of the cognitive radio networks depend on the sensing performance and can be maximized by reducing the sensing errors. In this work, we investigate the optimal sensing parameters of imperfect sensing for opportunistic spectrum access–based cognitive radio networks. The optimal sensing operating points are analyzed for different sensing durations and known primary user activities. First, the sum rate gain and sum rate loss are presented for the non-cooperative network, in terms of perfect channel sensing, and imperfect channel sensing, with and without optimal sensing pairs. Next, the trade-off between cooperative gain and cooperation overhead is examined for the multiuser cognitive radio networks. The sum rate is derived, using the optimal operating point, to investigate the cooperative sensing trade-off for different number of cooperative users in the multiuser cognitive radio network.